Prevention of acute immunological lung lesion in rats by decomplementing treatment - Carvalho, I. F. De (1969)
The intravenous administration of nephrotoxic antibody serum to rats produced a rapid and pronounced reduction in the serum complement level; this was observed before lung lesions became apparent. A total suppression of the acute immune lung change was observed in animals depleted of complement by treatment with heat-aggregated human γ-globulin or zymosan. Albeit the experimental evidence presented is of indirect nature, it suggests that the complement system is involved in the mediation of the acute pulmonary injury following injection of nephrotoxic antibody serum.